Genome Sequence of the Drosophila melanogaster Male-Killing Spiroplasma Strain MSRO Endosymbiont - Paredes, Juan C. (mBio, 2015)
Spiroplasmas are helical and motile members of a cell wall-less eubacterial group called Mollicutes. Although all spiroplasmas are associated with arthropods, they exhibit great diversity with respect to both their modes of transmission and their effects on their hosts; ranging from horizontally transmitted pathogens and commensals to endosymbionts that are transmitted transovarially (i.e., from mother to offspring). Here we provide the first genome sequence, along with proteomic validation, of an endosymbiotic inherited Spiroplasma bacterium, the Spiroplasma poulsonii MSRO strain harbored by Drosophila melanogaster. Comparison of the genome content of S. poulsonii with that of horizontally transmitted spiroplasmas indicates that S. poulsonii has lost many metabolic pathways and transporters, demonstrating a high level of interdependence with its insect host. Consistent with genome analysis, experimental studies showed that S. poulsonii metabolizes glucose but not trehalose. Notably, trehalose is more abundant than glucose in Drosophila hemolymph, and the inability to metabolize trehalose may prevent S. poulsonii from overproliferating. Our study identifies putative virulence genes, notably, those for a chitinase, the H(2)O(2)-producing glycerol-3-phosphate oxidase, and enzymes involved in the synthesis of the eukaryote-toxic lipid cardiolipin. S. poulsonii also expresses on the cell membrane one functional adhesion-related protein and two divergent spiralin proteins that have been implicated in insect cell invasion in other spiroplasmas. These lipoproteins may be involved in the colonization of the Drosophila germ line, ensuring S. poulsonii vertical transmission. The S. poulsonii genome is a valuable resource to explore the mechanisms of male killing and symbiont-mediated protection, two cardinal features of many facultative endosymbionts.